Crony capitalism : corruption and development in South Korea and the Philippines - Kang, David C. (David Chan-oong), 1965- (Cambridge studies in comparative politics., 2002)
"Why has the literature on Asian development not addressed the issue of money politics in Korea? How can we reconcile the view of an efficient developmental state in Korea before 1997 with reports of massive corruption and inefficiency in that same country in 1998 and 1999? Politics is central to the answer. In this book Kang makes two arguments. First, political - not economic - considerations dominated policy making in both Korea and the Philippines. Second, if there is a balance of power among a small and stable set of government and business elites, money politics can actually reduce transaction costs and promote growth. Focusing on the exchange of favors for bribes between state and business, Kang argues that politics drove policy choices, that bureaucrats were not autonomous from political interference in setting policy, and that business and political elites wrestled with each other over who would reap the rents to be had. Even in Korea, corruption was far greater than the conventional wisdom allows - so rampant was corruption that we cannot dismiss it; rather, we need to explain it."--Jacket